THEORY AND PRACTICE OF LOCAL HISTORY WORK AS A PSYCHOLOGICAL AND PEDAGOGICAL TECHNOLOGY OF PROVIDING PROFESSIONAL TRAINING OF STUDENTS IN GENERAL - Buhriy В.С. (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the anaysir of pedagogical Jeatures of regional work in connection with the type teaching at school. It was set that construction of educational process on the basis off regional wort was instrumental in the conscious choice ofprofession due to cognition by the schoolboys of the possibilities, participation in labour processes and creative work being informed about the prospecis of region.